Metaphoric expressions in Jordanian colloquial language; Linguistic approach - Al-Kashla, Zaid “Muhammad Naji” Yaqoub (Dirasat: Human and Social Sciences, 2025)
Objectives: This research aims to highlight the significance of the language used by Jordanian teenagers in shaping figurative expressions and their pragmatics in terms of both form and meaning. The study focuses on the discourse of figurative expressions and their usage domains within this demographic, following the principles of linguistic borrowing and economy. Methods: The study employs a descriptive-analytical method with a linguistic approach. It is divided into two main parts: the first part presents the discourse of contemporary figurative expression, and the second part analyzes the domains of this discourse's usage. Results: Among the prominent findings of the study are the contributions of contemporary figurative expression to the language in terms of both form and meaning. It emphasizes the value of expressive economy, the importance of linguistic borrowing in countering accusations of rigidity and stagnation in Arabic, and the flexibility of expressions in practical communication. Conclusions: The study traces the figurative expressions in the language of Jordanian teenagers through a linguistic approach. The research problem revolves around answering the following questions: How do we understand the mechanism of figurative expression formation? What is the significance of figurative expression usage in society? How do figurative expressions serve the Arabic language specifically and language in general? This is achieved by presenting the contemporary discourse of figurative expression and analyzing a range of expressions in various pragmatic domains of youth language.